New business models and value creation: a service science perspective - Minin, Alberto Di; Varaldo, Riccardo; Cinquini, Lino (Sxi - Springer per l'Innovazione / Sxi - Springer for Innovation, 2013)
The contemporary economic landscape features the prevalence of the service sector in economic systems, the pervasive servitisation of manufacturing, innovations in traditional business models and new value creation models, thanks to the new possibilities offered by the web, ICT and other enabling technologies. In this evolving context, this book provides qualified contributions on the topic of service science from a managerial perspective. A multidisciplinary perspective is adopted, dealing with both the structural-technological and dynamic-relational aspects of managing complexity. In addressing the contribution that service science can make to business value creation, this book covers relevant issues such as product servitisation, business modelling, value cocreation with customers, performance measures and the role of ICT. It also presents some innovative experiences of management models in service organisations operating in the environmental, energy and health-care sectors. This book aims to enhance the value of the results of research intertwined with the development of a new training curriculum started four years ago at the Scuola Superiore Sant'Anna of Pisa (Italy) with the evolution of the "Master in Management of Innovation" into the new "Master in Management, Innovation and Service Engineering" (MAINS).